PENGARUH MOTIVASI DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI PADA PT. KESUMA JAKARTA - Barlian, Ujang Cepi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2016)
Human resource is an investment which necessary for organization to reach its goals. One way to reach goals of organization is by developing human resources. The Development of human resources represent activities which need to be done by company, so that knowledge and ability of employees as according to work demand. One of the effort in human resources development is by knowing motivation which increases employees performance. This research conducted by observation, interview and distribution of questionnaire. Instrument tested by measuring its reliability and validity. To test interrelations and contribute factors that happened between variables used by simple regression. The results concluded that Motivation has an effect 38% to performance, this effect small significant categories.Â Keywords: Motivation, Organizational Climate, Officersâ Performance, PT Kesuma Jakarta